Epithelial‐to‐mesenchymal transition: immunohistochemical investigation of related molecules in canine cutaneous epithelial tumours. Issue 1 (19th January 2013) - Bongiovanni, Laura; D'Andrea, Alessandra; Romanucci, Mariarita; Malatesta, Daniela; Candolini, Melissa; Salda, Leonardo D.; Mechelli, Luca; Sforna, Monica; Brachelente, Chiara
<x xml:space="preserve">Abstract</x> Background – Epithelial‐to‐mesenchymal transition (EMT) is a multistep process, important in tumour invasion and metastasis, characterized by loss of epithelial markers, redistribution of β‐catenin and gain of mesenchymal markers. Hyposthesis/Objectives – Our aim was to investigate the immunohistochemical aberrant expression of cytokeratin, vimentin, survivin and heat shock protein 72 (Hsp72) in canine cutaneous epithelial tumours, to understand the association of expression of these molecules with features of malignancy and their role in the EMT phenotype. Methods – Ten canine squamous cell carcinomas (SCCs; one with lymph node metastasis), 30 canine hair follicle tumours (six pilomatricomas, eight infundibular keratinizing acanthomas, six trichoepitheliomas and 10 trichoblastomas) and five normal skin samples were investigated by immunohistochemistry using specific anti‐vimentin, ‐cytokeratin, ‐survivin and ‐Hsp72 antibodies. A semi‐quantitative method was used to analyse the results, as follows: 0 to <5%; ≥5 to <10%; ≥10 to <25%; and ≥25% of positive cells. Immunofluorescence was performed to investigate survivin–vimentin and survivin–Hsp72 colocalization in selected SCCs. Results – In malignant hair follicle tumours and SCCs, a reduced intensity of cytokeratin and increased survivin and Hsp72 expression were observed. In SCCs, loss of cytokeratin expression and vimentin immunolabelling, suggestive of the EMT phenotype, were evident in <5% of neoplastic cells in the front of tumour invasion. In the same areas, strong nuclear survivin and cytoplasmic Hsp72 staining was evident, often colocalizing. Only a few neoplastic cells in the front of tumour invasion showed vimentin–survivin colocalization. Conclusions and clinical importance – A possible simultaneous involvement of survivin and Hsp72 in tumour invasion and the multistep process of EMT of cutaneous epithelial tumours of dogs is suggested.